Infrared and Raman Spectroscopic Imaging. - Salzer, Reiner; Siesler, Heinz W. (Weinheim : Wiley-VCH, 2014)
This second edition of the successful ready reference is updated and revised with approximately 30% new content to reflect the numerous instrumental developments and improvements, as well as the significant expansion of this rapidly developing field. For example, the combination of IR imaging with AFM has enhanced the achievable lateral resolution by an order of magnitude down to a few hundred nanometers, thus launching a multiplicity of new applications in material science. Furthermore, Raman and IR spectroscopic imaging have become key technologies for the life sciences and today contribute.
Part II Biomedical ApplicationsChapter 3 Vibrational Spectroscopic Imaging of Soft Tissue; 3.1 Introduction; 3.1.1 Epithelium; 3.1.2 Connective Tissue and Extracellular Matrix; 3.1.3 Muscle Tissue; 3.1.4 Nervous Tissue; 3.2 Preparation of Soft Tissue for Vibrational Spectroscopic Imaging; 3.2.1 General Preparation Strategies; 3.2.2 Vibrational Spectra of Reference Material; 3.2.3 Preparation for FT-IR Imaging; 3.2.4 Preparation for Raman Imaging; 3.3 Applications to Soft Tissue; 3.3.1 Colon Tissue; 3.3.2 Brain Tissue and Brain Tumors; 3.3.2.1 Mouse Brains; 3.3.2.2 Primary Brain Tumors.
Print version record.
3.3.2.3 Secondary Brain Tumors.
Keywords: Infrared spectroscopy; Raman spectroscopy; SCIENCE -- Chemistry -- Analytic; Infrared spectroscopy; Raman spectroscopy; Electronic books